Mapping Students’ Mathematical Literacy Skills in Basic Geometry: A Study Based on Stacey and Turner’s Indicators - Ma’ruf, Abdul Hakim; Triyono, Ageng; Fauziah, Nazwa Rifa; Warohmah, Mawadah; Nurimani, Nurimani; Kusuma, Arie Purwa (AlphaMath : Journal of Mathematics Education, 2025)
Indonesia’s mathematical literacy achievement remains below the global average, indicating a continued need to improve these skills. This study aims to map the mathematical literacy abilities of eighth-grade students in basic geometry, particularly two-dimensional shapes, based on Stacey and Turner’s indicators: (1) formulating real-life situations mathematically; (2) using concepts, facts, procedures, and reasoning; and (3) interpreting, applying, and evaluating results. This research employs a descriptive qualitative approach, with data collected through mathematical literacy tests, analysis of student responses, and in-depth interviews across three ability categories (high, medium, low). The categorization of subjects facilitates a more structured and in-depth analysis process. The findings show that most students fall into the medium category, while fewer are in the high and low categories. Based on the indicators, the main weaknesses are in students’ ability to formulate real-life situations mathematically and to evaluate results; these findings are consistent with PISA studies, which also highlight these two aspects as major weaknesses in Indonesian students’ mathematical literacy. High-ability students demonstrate mastery of all indicators, while medium-ability students generally complete only part of the process and rarely reflect on their answers. Low-ability students have difficulties in formulating real-life situations, using concepts, and are unable to evaluate results. This study confirms that the primary weaknesses are in formulating problems and evaluating results, in line with PISA findings. The implications of this study highlight the need for contextual and reflective mathematics learning, as well as strengthened teacher training in developing mathematical literacy assessments.